2010
DOI: 10.1258/ijsa.2009.008494
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycoplasma genitalium among HIV-infected men in São Paulo city detected by realtime polymerase chain reaction

Abstract: Genital mycoplasmas are natural inhabitants of the male urethra and are potentially pathogenic species playing an aetiological role in both genital infections and male infertility. This study aims to determine the presence of Mycoplasma genitalium DNA in urine samples of HIV-1-infected men in São Paulo city. Realtime polymerase chain reaction (PCR) was performed using the primers My-ins and Mgso-2 and the Taqman probe Mgen-P1 as described previously. A total of 223 HIV-1-infected men were tested with a mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
2
9
3
Order By: Relevance
“…This result was different from the result of da Costa et al 13 study that found HIV male patients with positive M. genitalium often practice oral sex (38%).…”
contrasting
confidence: 96%
See 4 more Smart Citations
“…This result was different from the result of da Costa et al 13 study that found HIV male patients with positive M. genitalium often practice oral sex (38%).…”
contrasting
confidence: 96%
“…This result is different from that of the da Costa et al 13 study which revealed infection of M. genitalium in HIV positive males were most common in men who have sex with men (MSM), i.e. 77%.…”
contrasting
confidence: 87%
See 3 more Smart Citations